Conducting the "Green Book of Ukraine": problems and solutions (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
This arti cle concentrates on the actual phytosozological task the improvement of scientific principles and the development of new forms of conservation of the vegetable world in order to ensure the spontaneous development of phytobiota. It is highlighted that one of the mechanisms for ensuring the protection of a rare phytocoenofund is the conducting of the “Green Book of Ukraine”. In connection with the preparation of its second, as the state document of the publication, it becomes evident the need for a critical review of the lists of rare syntaxa, their sozological status, the establishment of the latest phytocoenological studies of rare phytocoenodiversity that needs protection, determination of the level of natural and anthropic transformation of rare plant co mmunities. It is determined that as a result of the critical analysis of the syntaxonomic composition of the rarity phytocoenodiversity of Ukraine and the releves of their phytocoenoses, a number of associations have been identified that need to be clarifi ed. The list of rarity phytocoenofund included syntaxa, the communities of which, as shown by field studies, probably disappeared from their localities due to the effects of natural or anthropic factors. It is established 133 rare associations that include d in the “Green Book of Ukraine”, and which require clarification: 90 forest, 2 shrub, 29 steppe, 5 outcrops and sand, 2 meadow, 4 marsh, 1 water are found among the rare associations included in the Green Book of Ukraine. The authors propose to add 36 new associations to the new edition of the "Green Book of Ukraine" and justify their sozological value. The article contains their list and scientific botanical characteristic. The authors consider that the system of environmental measures for r are plant communities should be systematic, taking into account biological, phytocoenotic, ecological factors, as well as environmental conditions of the region and the level of anthropogenic influence, functional and structural features of rare communitie s, and the degree of the sozological value.
Keywords: Green Book of Ukraine, rare plant communities, problems, solutions.